4t - 8 + 12 = 3 - 4t- 11

*4t - 8 + 12 = 3 - 4t- 11*

You want to collect all of the "t" terms on one side of the equation and all of the other terms on the other side until you end up with t = something. This process is called "Solving for t".

Add the constant terms on each side of the equation: -8+12=4, 3-11=-8

4t + 4 = -4t - 8

Subtract 4 from both sides:

4t + 4 - 4 = -4t - 8 - 4

4t = -4t - 12 (4-4=0, -8-4=-12)

Add 4t to both sides:

4t + 4t = -4t + 4t - 12

8t = -12 (4t+4t=8t, -4t+4t=0)

Divide both sides by 8

**t = -12/8 = -3/2**

**Check:**

4t - 8 + 12 = 3 - 4t- 11

4(-3/2) - 8 + 12 = 3 - 4(-3/2) - 11

-6 - 8 + 12 = 3 + 6 - 11

-2 = -2 Check!